2005
DOI: 10.1302/0301-620x.87b1.14584
|View full text |Cite
|
Sign up to set email alerts
|

Elevated, straight-arm traction for supracondylar fractures of the humerus in children

Abstract: , 112 children with a closed displaced supracondylar fracture of the humerus without vascular deficit, were managed by elevated, straight-arm traction for a mean of 22 days. The final outcome was assessed using clinical (flexion-extension arc, carrying angle and residual rotational deformity) and radiographic (metaphyseal-diaphyseal angle and humerocapitellar angle) criteria. Excellent results were achieved in 71 (63%) patients, 33 (29%) had good results, 5 (4.4%) fair, and 3 (2.6%) poor. All patients with fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 28 publications
2
20
0
3
Order By: Relevance
“…For patients over 10 years of age, chips of excised bone can be inserted on the dorsal side to avoid fixation in hyperextension. These findings are in agreement with those of Gadgil et al [19] who reported that patients older than 10 years of age treated with straightarm traction after distal humeral supracondylar fracture had some terminal restriction of flexion, indicating that the remodeling capacity is limited in this age group.…”
Section: Discussionsupporting
confidence: 93%
“…For patients over 10 years of age, chips of excised bone can be inserted on the dorsal side to avoid fixation in hyperextension. These findings are in agreement with those of Gadgil et al [19] who reported that patients older than 10 years of age treated with straightarm traction after distal humeral supracondylar fracture had some terminal restriction of flexion, indicating that the remodeling capacity is limited in this age group.…”
Section: Discussionsupporting
confidence: 93%
“…First described by Dunlop, 18 various authors have since advocated the use of straight arm skin traction. 18,27,37 They were able to produced predominantly good or excellent functional results, with only a few cases of cubitus varus, and no iatrogenic nerve palsies.…”
Section: Tractionmentioning
confidence: 99%
“…Matsuzaki et al [18] in 2004 reported on 193 patients treated with skeletal traction and bracing with a cubitus varus incidence of 2%. Gadgill et al [19] in 2005 reported good to excellent results in 92% of 112 children (younger than 10 years) with supracondylar fractures treated with straight-arm traction. With these continuing good results, should we really be disregarding skeletal traction as a treatment modality?…”
Section: Discussionmentioning
confidence: 99%